(untitled) (Journal of Tikapur Multiple Campus, 2025)
This article examines the transformative impact of Information and Communication Technology (ICT) in ELT classrooms. ICT opens the door for effective learning, and makes students engage in discussions with peers and educators in diversified classrooms. Teachers can vary their teaching activities changing their teaching style from teacher-centered to learner-centered through multimedia resources in classrooms. This paper is based on phenomenological methodology. This study has explored the perceptions of the use of ICT in ELT by four secondary-level English teachers from the Kathmandu and Lalitpur districts. The study’s findings reveal the importance of using particular ICT tools that have great effectiveness for both teachers and students in ELT classrooms. Hence, this study emphasizes the integration of some ICT tools (like Mobile, Smart TV, Laptop and Projector, Speaker, and Smart Board) enhance the students’ quality learning in the ELT classroom. Finally, this study indicates ICT can make the students active and interactive to accelerate their learning capability. To lessen the challenges of ICT implementation in a classroom, there is a need for consideration of other aspects of ICT integration regarding strategic planning and policy-making from MoE.